Macrocycles: Recent Advances in Synthesis, Reactivity, and Medicinal Chemistry - Barancheshme, Maryam; kakouei, Mozhan; Khaksar, Samad (International Pharmacy Acta, 2018)
Introduction: A cyclic compound is common motif in natural product structures. Cyclic peptides, a vast subset of natural products, display a wide variety of biological activities. Owing to their size, cyclic peptides are particularly attractive scaffolds for interrogating challenging biomolecular interactions, such as those at protein–protein interfaces. Methods and Results: This review takes an overview of the literature for the synthesis of peptide and non-peptide macrocycles, concentrating on advances in the last five years up to the end of 2017. These methods are clustered by strategies for preparation and further derivatization of preformed macrocycle-containing building blocks. Examples of the use of macrocycles in medicinal chemistry are reported, including a collation of macrocycle derivatives appearing in recent patents for medicinal chemistry applications. Conclusions: This review aims to provide an overview of the extensive recent studies involving macrocycles in synthesis and medicinal chemistry and to highlight the continuing challenges.